2021
DOI: 10.1002/celc.202001416
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Concave Zinc‐Doped Co3O4 Nanosheets/Carbon Composites as Ultrahigh Capacity Anode Materials for Lithium‐Ion Batteries

Abstract: Composition‐structure strategy is an effective method to improve the electrochemical performance of lithium‐ion batteries (LIBs). Ideal active materials combined with unique structure can lead to potential candidates for next‐generation LIB anode materials. In this research, we designed a hollow concave Zn‐doped Co3O4 nanosheets/carbon composites as active electrodes for LIBs. The hollow concave structure could shorten the path length of Li+ and electron transfer. The interconnected Co3O4 nanosheets could cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 75 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…According to the conversion reaction with lithium ions, transition metal oxides are promising anodes for LIBs due to their high theoretical capacities (500-1000 mAh/g) [18,19]. To achieve practical application, cobalt oxides, including CoO and Co 3 O 4 , have been intensely investigated to solve the intrinsic disadvantages of volume change and low electrical conductivity during the discharge-charge process [20][21][22][23]. As a precursor, Co(OH) 2 has always been used to prepare cobalt-based oxides by heat treatment [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…According to the conversion reaction with lithium ions, transition metal oxides are promising anodes for LIBs due to their high theoretical capacities (500-1000 mAh/g) [18,19]. To achieve practical application, cobalt oxides, including CoO and Co 3 O 4 , have been intensely investigated to solve the intrinsic disadvantages of volume change and low electrical conductivity during the discharge-charge process [20][21][22][23]. As a precursor, Co(OH) 2 has always been used to prepare cobalt-based oxides by heat treatment [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…The additional peaks at binding energy of 532.7 and 534.3 eV are attributed to the absorbed H 2 O on the sample. 35,36 The C 1s XPS spectrum shown in Figure 4D presents the sp 2bonded carbon (C═C) peak at 284.2 eV, C N and C C peaks at 285.1 eV, and C═O peak at 288 eV. 37,38 The presence of graphitic carbon in A300NF is confirmed by the highest intensity of C C peak among those peaks (Figure 4D).…”
Section: Resultsmentioning
confidence: 91%
“…The metal‐oxygen peaks appear at 530.8 eV in the O 1s spectrum, as shown in Figure 4C. The additional peaks at binding energy of 532.7 and 534.3 eV are attributed to the absorbed H 2 O on the sample 35,36 . The C 1s XPS spectrum shown in Figure 4D presents the sp 2 ‐bonded carbon (C═C) peak at 284.2 eV, CN and CC peaks at 285.1 eV, and C═O peak at 288 eV 37,38 .…”
Section: Resultsmentioning
confidence: 94%
“…The Zn-doped Co 3 O 4 nanocomposites with a hollow concave structure displayed excellent rate capability and high specific capacities with stable cyclability. The outstanding electrochemical performance originated from the unique hollow concave structure and the defects induced by Zn doping, which could effectively improve the electronic structure of Co 3 O 4 composites and then enhance the electrochemical reaction kinetics [ 36 ]. Wu et al reported that the binary transition metal Cu 3.8 Ni was doped with CoO and MnO.…”
Section: Hybridization Between the Transition Metal And Transition Me...mentioning
confidence: 99%